Communicating for success - Kossen, Christopher , 1963-; Kiernan, Eleanor F.; Lawrence, Jill E. (Frenchs Forest, Australia : Pearson Australia, 2013)
Communication is central to being human and the way we experience life. The aim of this book is to assist students in further developing and refining communication skills in an effort to optimise performance across a range of pursuits, both academic and otherwise. Key performance skills dealt with in this book relate to academic performance, professional performance and competencies for dealing with people, as well as cultivating productive relationships. The book has a strong focus on academic skills with chapters covering university culture and transition skills, academic writing including research and referencing, and communication theory. Additionally, it examines skills used in university studies which are also applicable to personal and professional contexts, including areas relating to digital, oral and nonverbal communication as well as issues around persuasion, argument and ethics.
1. Introduction -- 2. University culture and transition skills -- 3. Academic writing -- 4. Research and referencing -- 5. Communication theory -- 6. Perception, audience analysis and task analysis -- 7. Intercultural communication -- 8. Social media-untangling the web -- 9. Oral communication: presentations and interviews -- 10. The power of nonverbal communication -- 11. Think smarter: critical thinking and argument -- 12. Interpersonal and professional communication -- 13. Group and organisational communication -- 14. Communication barriers
Includes bibliographical references and index
Keywords: Business communication; Communication; Interpersonal communication; Nonverbal communication; Oral communication; Written communication